0303 Heart Rate and Systolic Blood Pressure Increase During Experimental Sleep Restriction. (27th May 2020) - Reichenberger, D A; Strayer, S M; Mathew, G M; Buxton, O M; Chang, A
Abstract: Introduction: Experimental sleep restriction is associated with elevated daytime cardiac activity, including heart rate (HR) and blood pressure (BP). However, some studies have found changes in systolic (SBP) but not diastolic blood pressure (DBP) or found changes in neither. Although findings are mixed, there may be a dose-response effect of cumulative sleep loss on daytime cardiac activity, such that HR and BP increase above basal levels with additional nights of insufficient sleep. This study examined changes in cardiac activity during experimental sleep restriction. Methods: We used multilevel models with random effects for individuals to analyze data from 15 healthy males (M=22.3 years old, SD=2.8) in an 11-day inpatient protocol consisting of three nights of 10-hour/night baseline sleep opportunity, five nights of sleep restriction (5-hour/night sleep opportunity), and then two recovery nights (10-hour/night sleep opportunity). HR and BP were measured approximately every two hours during wake. Results: HR increased 0.75 beats/minute with each successive night of sleep restriction (SE=0.18, p<0.001). HR was 5.13 beats/minute higher during the recovery condition than during baseline or sleep restriction (SE=1.05, p<0.001). During sleep restriction only, HR was lower in the later morning and evening compared to the earliest morning timepoint of the day, F(10, 743)=10.44, p<0.001. SBP increased 0.33 mmHg following each successive night of sleep restriction (SE=0.16, p=0.041); however, SBP was only marginally higher during the sleep restriction condition than during baseline (b=1.90, SE=1.09, p=0.082). Conclusion: Our findings suggest that HR and SBP increase with each additional day of experimental sleep restriction, even after accounting for diurnal effects on HR and SBP. HR did not recover to baseline levels following a night of recovery sleep, suggesting that longer recovery sleep may be necessary to recover from a week of sleep restriction. Support: Grant UL1TR000127 (Chang PI), Clinical and Translational Science Institute; College of Health and Human Development at Pennsylvania State University.